Coating method of ceramic coating for relief etching pot

By using ceramic coatings including primer and facial paint on the convex etching cooker, and using sandblast treatment, nitrogen blowing, laser drying and other technologies, the environmental protection problems of PFAS materials in existing technologies have been solved. Overwriting and excellent performance.

CN119346405AInactive Publication Date: 2025-01-24SHANGHAI EXCILON NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411944598.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing etching pots mainly use polytetrafluoroethylene non-stick coatings. However, due to the environmental protection of PFAS, alternatives to wear-resistant, stain-resistant and corrosion-resistant ceramic non-stick coatings are sought to meet the needs of letterpress etching pots.

Method used

A ceramic coating including primer and topcoat is used, and through steps such as sandblasting, nitrogen purging, laser drying, etching and polishing, a coating with excellent wear resistance, corrosion resistance and high temperature resistance is formed.

Benefits of technology

The high -efficiency coating of ceramic coatings on the carved pot is significantly improved, significantly improved the adhesion, abrasion resistance, corrosion resistance and chemical resistance of the coating, and extended the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a coating method of a ceramic coating for a relief etching pot, and belongs to the technical field of ceramic coatings. The adhesive force of the coating is remarkably improved through the fine sand blasting treatment, nitrogen purging and other pretreatment steps, uniform drying of primer and finish paint is ensured through application of the laser drying method, and the problem that the coating is not uniform possibly caused by a traditional drying method is solved; etching treatment and polishing not only improve the attractiveness of the coating, but also enhance the wear resistance and corrosion resistance of the coating, and baking curing treatment further improves the hardness and chemical resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic coatings and relates to a coating method of ceramic coatings for relief etching pots. Background Art

[0002] The etched pots on the market are all gravure etched pots. The purpose is to use the raised stainless steel mesh frame to protect the polytetrafluoroethylene non-stick coating applied to the recessed area, circumvent its poor wear resistance and scratch resistance, and extend the service life of the kitchenware. The feasibility of letterpress etched pots lies in the fact that when using ceramic non-stick coating, there is no need to use the raised stainless steel mesh frame. The wear resistance and scratch resistance of the coating itself are excellent enough to meet the cooking needs of kitchenware products. The purpose of etching is to form a texture on the kitchenware, which meets the user's needs for appearance while maintaining the excellent non-stick performance of the coating.

[0003] Conventional etched pots are coated with polytetrafluoroethylene non-stick coating, and polytetrafluoroethylene belongs to PFAS. Currently, European and American countries are actively legislating to ban or restrict the use of materials and products containing PFAS. Therefore, ceramic non-stick coating is the best alternative to polytetrafluoroethylene non-stick coating. Summary of the invention

[0004] The object of the present invention is to provide a coating method of ceramic coating for relief etching pot, which has the characteristics of wear resistance, stain resistance and corrosion resistance.

[0005] The purpose of the present invention can be achieved by the following technical solutions: A coating method for ceramic coating for relief etching pots, the ceramic coating comprising a primer and a topcoat, the coating method comprising the following specific steps: S1.1: The pot surface is first sandblasted with 80-mesh brown corundum at a distance of 70 mm and an angle of 80°, and then sandblasted with glass beads for a second time at a distance of 50 mm and an angle of 60° to form a surface with a roughness of Ra=3.0~4.0. After the second sandblasting, nitrogen is purged for 5 minutes. After purging, primer is sprayed on the pot surface, and the primer is dried using a laser drying method; S1.2: etching the surface of the pot after the primer is dried to obtain a relief etching pot, polishing and grinding the pot after etching, and nitrogen is purged again for 0.5h, and then topcoat is sprayed on the polished and ground pot surface after purging; S1.3: The pot after spraying the topcoat is baked and cured to complete the coating of the ceramic coating.

[0006] Furthermore, the primer formula is, by mass percentage, 20-30% hydrophilic modified nano silica sol, 5-15% inorganic pigment, 5-10% silica filler, 5-10% hollow glass microspheres, 30-40% ethyl orthosilicate, 1-5% formic acid, and 5-10% deionized water; The preparation method of hydrophilic modified nano silica sol is as follows: Aminopropyl triethoxysilane and nano-silica sol are mixed in a volume ratio of 1:10, and then 0.2wt% of 1M ammonia water is added, and the mixture is stirred at a speed of 150r / min. The temperature is raised to 40°C while stirring, and the stirring time is 2h. After the temperature is maintained at 40°C, 2wt% of polyethylene glycol 2000 is added, and the speed is increased to 200r / min. The stirring is continued for 0.5h. After the stirring is completed, the mixture is cooled to room temperature, and the mixture is first washed with ethanol and then washed with deionized water to obtain a hydrophilic modified nano-silica sol; The preparation method of the primer is as follows: S2.1: Grind the inorganic pigment and silica filler in a ball mill at a ratio of 400 rpm at 20-25°C for 1-2 hours to obtain a mixed powder; S2.2: Disperse the mixed powder and hollow glass microspheres in the hydrophilic modified nano-silica sol, and ultrasonicate for 2-3 hours to obtain the primer A component after dispersion; S2.3: Take ethyl orthosilicate as primer B component according to the proportion, put formic acid and deionized water into a mixer and stir at a speed of 200 r / min for 3 to 5 minutes to obtain primer C component; S2.4: Before using the primer, add the primer C component to the primer B component, mix well, then add the primer B+C components to the primer A component, and finally continue to stir the mixture at a speed of 120r / min for 5h, and filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the primer.

[0007] Furthermore, the topcoat formula is, by mass percentage, 30-40% nano silica sol, 40-50% methyltrimethoxysilane, 1-5% formic acid, 1-5% polydimethylsiloxane, and 10-20% deionized water; The preparation method of the topcoat is as follows: According to the proportion, nano-silica sol is respectively used as the topcoat component A, formic acid and deionized water are mixed to obtain the topcoat component C, polydimethylsiloxane and methyltrimethoxysilane are mixed to obtain the topcoat component B, the topcoat component C is added to the topcoat component B before the topcoat is used, and after the topcoat B+C components are evenly mixed, the mixed liquid is finally put into a blender and stirred at a speed of 120 r / min for 4 to 6 hours, and the stirred mixture is filtered through a filter cloth with a mesh size of 300 or more to obtain the topcoat.

[0008] Furthermore, the purge flow rate of nitrogen in S1.1 is 10 m / s.

[0009] Furthermore, the spraying parameters of the primer in S1.1 are a spraying distance of 30 cm and a spraying rate of 60 mm / s.

[0010] Furthermore, the parameters of the laser drying method in S1.1 are: laser power 300 W, temperature 50° C., and irradiation time 3 to 5 min.

[0011] Furthermore, the parameters of the polishing and grinding process in S1.2 are to use a grinding head composed of 2000 mesh elastic modules and grind at 0.3-0.5 MPa for 3-5 seconds.

[0012] Furthermore, the purge flow rate of nitrogen in S1.2 is 10 m / s.

[0013] Furthermore, the spraying parameters of the topcoat in S1.2 are a spraying distance of 30 cm and a spraying rate of 70 mm / s.

[0014] Furthermore, the parameters for the baking and curing in S1.3 are first baking at 100° C. for 7 minutes in the low temperature section and then baking at 300° C. for 15 minutes.

[0015] The manufacturing process of the relief etching pot is to first sandblast the stainless steel surface to achieve the required roughness, spray the primer and dry the surface, then use laser etching to expose the concave stainless steel grid texture, and use very light polishing equipment to smooth the etched edges, but do not cause obvious damage to the coating primer. After removing the dust, the topcoat is evenly sprayed on the entire surface to form a continuous and uninterrupted paint film.

[0016] In the coating process of ceramic coating, the present invention first uses steel sand for the first sandblasting treatment. The setting of the sandblasting distance and angle ensures the uniformity and strength of the treatment effect, effectively removes the oxide scale, rust and oil stains on the surface of the pot, and lays a good foundation for the subsequent coating adhesion; then glass beads are used for more refined sandblasting treatment to further refine the surface roughness, increase the adhesion area of ​​the coating, and enhance the bonding force between the coating and the pot surface. After the sandblasting is completed, the tiny particles and impurities remaining on the surface after sandblasting are removed by nitrogen purge to ensure the absolute cleanliness of the pot surface before the primer is sprayed. The uniform spraying of the primer provides a good foundation for the subsequent etching treatment and topcoat spraying, and the laser drying method ensures the rapid and uniform drying of the primer, avoiding the coating defects that may be caused by the traditional drying method. After the primer is dried, the pot surface is etched to form a relief effect. The polishing and grinding after etching further improves the flatness and smoothness of the coating, creating favorable conditions for the uniform spraying of the topcoat. The uniform spraying of the topcoat not only enhances the overall aesthetics of the coating, but also further improves the wear resistance, corrosion resistance and high temperature resistance of the coating. Finally, the solvent in the coating is fully volatilized through baking and curing treatment, and the coating is denser and more stable. This step significantly improves the hardness and chemical resistance of the coating, ensuring that the coating can maintain excellent performance for a long time during use.

[0017] The hydrophilic modified nano-silica sol, silica filler and other ingredients in the primer formula can significantly improve the adhesion between the primer and the surface of the pot through its nano-scale small size effect and surface effect. This enhanced adhesion helps prevent the coating from flaking or falling off during use and prolongs its service life; the hollow glass microspheres (≤10μm) in the primer can reduce the density and wear resistance of the coating, making the coating easier to powderize during laser etching and forming a neater cutting edge; ethyl orthosilicate can reduce the content of hydrophobic groups on the surface of the coating, making it easier to re-coat the topcoat after the primer has dried.

[0018] The surface of hydrophilic modified nano silica sol carries a large number of hydrophilic groups, which can form hydrogen bonds with water molecules, thereby significantly improving the wettability of the coating. This allows the primer to cover the surface of the pot more evenly during the spraying process, reducing splashing and sagging during the spraying process. In addition, improving the hydrophilicity of the coating surface is also conducive to the recoating of the topcoat after the primer is dry. The small size effect and surface effect of the nanoparticles enable them to penetrate into the tiny pores on the surface of the pot to form a mechanical locking effect. At the same time, the introduction of hydrophilic modified nano silica sol also increases the chemical bonding force between the primer and the surface of the pot, thereby significantly improving the adhesion of the coating.

[0019] The molecular structure of aminopropyltriethoxysilane APTES contains an aminopropyl group and a hydrolyzable ethoxysilane group. During the modification process, the ethoxysilane group of APTES will undergo a condensation reaction with the hydroxyl groups on the surface of the nano-silica sol to form a strong silicon-oxygen bond (Si-O-Si). At the same time, the aminopropyl part of APTES faces the outside of the sol, providing more active sites for the modification reaction. Adding ammonia water as a catalyst further promotes the hydrolysis and condensation reaction of APTES. Ammonia water can also neutralize the acidic substances produced by hydrolysis and maintain the appropriate pH value of the reaction system, which is conducive to the reaction of APTES with the hydroxyl groups on the surface of the nano-silica sol. At the same time, ammonia water itself has a certain hydrophilicity, and its presence may enhance the hydrophilicity of the sol to a certain extent.

[0020] In the modification step, polyethylene glycol 2000 is adsorbed on the surface of the nano-silica sol through physical or chemical effects, and can also react with the aminopropyl part of APTES to further introduce a large number of hydrophilic groups; the long chain structure of polyethylene glycol 2000 also helps to form a hydrophilic protective layer on the surface of the nano-silica sol, preventing the agglomeration of sol particles and improving its dispersion stability.

[0021] The modified nano-silica sol is washed with ethanol and deionized water in sequence to remove unreacted APTES, ammonia water and possible by-products. The washing process helps to purify the sol and improve the effect of its hydrophilic modification.

[0022] As a key component in the topcoat formula, the addition of nano-silica sol significantly improves the hardness and wear resistance of the topcoat. The high specific surface area and strong interaction force of nanoparticles make the coating surface denser, which can effectively resist scratches and wear, and extend the service life of the pot; methyltrimethoxysilane, as a silane coupling agent, not only enhances the internal bonding force of the coating, but also improves the isolation performance of the coating from the external environment. Polydimethylsiloxane (PDMS) has good chemical stability and weather resistance, and can maintain the integrity and performance of the coating under harsh conditions. The synergistic effect of these two ingredients makes the topcoat have excellent weather resistance and chemical stability.

[0023] Beneficial effects of the present invention: (1) The present invention significantly improves the adhesion of the coating through pretreatment steps such as meticulous sandblasting and nitrogen purging. The application of laser drying method ensures uniform drying of the primer and topcoat, avoiding the problem of uneven coating that may be caused by traditional drying methods. Etching and polishing not only improve the aesthetics of the coating but also enhance the wear resistance and corrosion resistance of the coating. The baking and curing treatment further improves the hardness and chemical resistance of the coating. (2) The present invention performs hydrophilic modification on the nano-silica sol. APTES and the nano-silica sol are mixed in a certain proportion, and the ethoxysilane groups of APTES begin to undergo condensation reaction with the hydroxyl groups on the surface of the nano-silica sol. Ammonia water is added as a catalyst to accelerate the hydrolysis and condensation reactions. While maintaining the temperature and stirring, the aminopropyl part of APTES faces the outside of the sol, providing active sites for the subsequent adsorption or reaction of polyethylene glycol 2000. After the addition of polyethylene glycol 2000, the hydrophilic groups on its molecular chain are introduced into the surface of the nano-silica sol through physical or chemical effects, which significantly enhances the hydrophilic properties of the sol. DETAILED DESCRIPTION

[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0025] Primer ratio 1: hydrophilic modified nano silica sol 30%, inorganic pigment 10%, silica filler 5%, hollow glass microsphere 5%, ethyl orthosilicate 40%, formic acid 5%, deionized water 5%; Primer ratio 2: hydrophilic modified nano silica sol 20%, inorganic pigment 15%, silica filler 10%, hollow glass microsphere 10%, ethyl orthosilicate 30%, formic acid 5%, deionized water 10%; Primer ratio 3: hydrophilic modified nano silica sol 25%, inorganic pigment 5%, silica filler 10%, hollow glass microspheres 10%, ethyl orthosilicate 40%, formic acid 1%, deionized water 9%; Topcoat ratio 1: 30% nano silica sol, 40% methyltrimethoxysilane, 5% formic acid, 5% polydimethylsiloxane, 20% deionized water; Topcoat ratio 2: nano silica sol 40%, methyltrimethoxysilane 40%, formic acid 1%, polydimethylsiloxane 4%, deionized water 15%; Topcoat ratio 3: nano silica sol 30%, methyltrimethoxysilane 50%, formic acid 5%, polydimethylsiloxane 5%, deionized water 10%; The preparation method of hydrophilic modified nano silica sol is as follows: Aminopropyltriethoxysilane and nano-silica sol were mixed in a volume ratio of 1:10, and then 0.2wt% of 1M ammonia water was added, and the mixture was stirred at a speed of 150r / min. The temperature was raised to 40°C while stirring, and the stirring time was 2h. After maintaining the temperature at 40°C, 2wt% of polyethylene glycol 2000 was added, and the speed was increased to 200r / min. The stirring was continued for 0.5h. After the stirring was completed, the mixture was cooled to room temperature, washed with ethanol first, and then with deionized water to obtain a hydrophilic modified nano-silica sol.

[0026] Example 1 The primer preparation method is as follows, S2.1: grind the inorganic pigment and silica filler in a ball mill at a ratio of 1 to the primer at 25°C at a speed of 400 r / min for 2 h to obtain a mixed powder; S2.2: Disperse the mixed powder and hollow glass microspheres in the hydrophilic modified nano-silica sol, and ultrasonicate for 2 h to obtain the primer A component after dispersion; S2.3: According to the primer ratio 1, ethyl orthosilicate is used as the primer B component, formic acid and deionized water are put into a mixer and stirred at a speed of 200 r / min for 5 minutes to obtain a primer C component; S2.4: Before using the primer, add the primer C component to the primer B component, mix well, then add the primer B+C components to the primer A component, and finally continue to stir the mixture at a speed of 120r / min for 5h, and filter the stirred mixture with a filter cloth of 300 mesh or more to obtain the primer; The topcoat preparation method is as follows: According to the topcoat ratio of 1, nano silica sol is used as topcoat component A, formic acid and deionized water are mixed to obtain topcoat component C, polydimethylsiloxane and methyltrimethoxysilane are mixed to obtain topcoat component B, and before using the topcoat, the topcoat component C is added to the topcoat component B, and after mixing evenly, the topcoat B+C components are added to the topcoat component A, and finally the mixed liquid is put into a blender and stirred at a speed of 120r / min for 5 hours, and the stirred mixture is filtered using a filter cloth with a mesh size of 300 or more to obtain the topcoat.

[0027] The specific steps of the coating method are as follows: S1.1: The pot surface is first sandblasted with 80-mesh brown corundum at a distance of 70 mm and a blasting angle of 80°. Glass beads are then used for a second sandblasting at a distance of 50 mm and a blasting angle of 60° to form a surface with a roughness of Ra=3.0. After the second sandblasting, nitrogen is purged for 0.5 h at a nitrogen purging flow rate of 10 m / s. After purging, primer is sprayed on the pot surface at a spraying distance of 30 cm and a spraying rate of 60 mm / s. The primer is dried by laser drying method at a laser power of 300 W, a temperature of 50°C, and an irradiation time of 4 min. S1.2: Etching the surface of the pot after the primer is dried to obtain a relief etched pot, and then polishing and grinding are performed. The polishing and grinding parameters are: using a grinding head composed of 2000 mesh elastic modules to grind at 0.3 MPa for 4 seconds, and then purging with nitrogen for 5 minutes. The nitrogen purge flow rate is 10 m / s. After purging, spraying the topcoat on the polished and ground pot surface. The spraying parameters of the topcoat are spraying distance 30 cm and spraying rate 70 mm / s. S1.3: The pot after spraying the topcoat is baked and cured. The baking and curing parameters are first baked at 100°C for 7 minutes at a low temperature, and then baked at 300°C for 15 minutes to complete the coating of the ceramic coating.

[0028] Example 2 The primer preparation method is as follows, S2.1: grind the inorganic pigment and silica filler in a ball mill at a ratio of 2 to the primer at 20°C, with the speed of the ball mill being 400 r / min and the grinding time being 2 h to obtain a mixed powder; S2.2: Disperse the mixed powder and hollow glass microspheres in the hydrophilic modified nano-silica sol, and ultrasonicate for 3 h to obtain the primer A component after dispersion; S2.3: According to the primer ratio 2, ethyl orthosilicate is used as the primer B component, formic acid and deionized water are put into a mixer and stirred at a speed of 200 r / min for 5 minutes to obtain a primer C component; S2.4: Before using the primer, add the primer C component to the primer B component, mix well, then add the primer B+C components to the primer A component, and finally continue to stir the mixture at a speed of 120r / min for 5h, and filter the stirred mixture with a filter cloth of 300 mesh or more to obtain the primer; The topcoat preparation method is as follows: According to the topcoat ratio of 2, nano silica sol is used as topcoat component A, formic acid and deionized water are mixed to obtain topcoat component C, polydimethylsiloxane and methyltrimethoxysilane are mixed to obtain topcoat component B, and before using the topcoat, the topcoat component C is added to the topcoat component B, and after mixing evenly, the topcoat B+C components are added to the topcoat component A, and finally the mixed liquid is put into a blender and stirred at a speed of 120r / min for 4 hours, and the stirred mixture is filtered using a filter cloth with a mesh size of 300 or more to obtain the topcoat.

[0029] The specific steps of the coating method are as follows: S1.1: The pot surface is first sandblasted with 80-mesh brown corundum at a distance of 70 mm and a blasting angle of 80°. Glass beads are then used for a second sandblasting at a distance of 50 mm and a blasting angle of 60° to form a surface with a roughness of Ra=4.0. After the second sandblasting, nitrogen is purged for 0.5 h at a nitrogen purging flow rate of 10 m / s. After purging, primer is sprayed on the pot surface at a spraying distance of 30 cm and a spraying rate of 60 mm / s. The primer is dried by laser drying at a laser power of 300 W, a temperature of 50°C, and an irradiation time of 3 min. S1.2: Etching the surface of the pot after the primer is dried to obtain a relief etched pot, and then polishing and grinding are performed. The polishing and grinding parameters are: using a grinding head composed of 2000 mesh elastic modules to grind at 0.5 MPa for 3 seconds, and then purging with nitrogen for 5 minutes. The nitrogen purge flow rate is 10 m / s. After purging, spraying the topcoat on the polished and ground pot surface. The spraying parameters of the topcoat are spraying distance 30 cm and spraying rate 70 mm / s. S1.3: The pot after spraying the topcoat is baked and cured. The baking and curing parameters are first baked at 100°C for 7 minutes at a low temperature, and then baked at 300°C for 15 minutes to complete the coating of the ceramic coating.

[0030] Example 3 The primer preparation method is as follows, S2.1: grind the inorganic pigment and silica filler in a ball mill at a primer ratio of 3 at 25°C, with a ball mill speed of 400 r / min and a grinding time of 1 h to obtain a mixed powder; S2.2: Disperse the mixed powder and hollow glass microspheres in the hydrophilic modified nano-silica sol, and ultrasonicate for 2 h to obtain the primer A component after dispersion; S2.3: According to the primer ratio 3, ethyl orthosilicate is used as the primer B component, formic acid and deionized water are put into a mixer and stirred at a speed of 200 r / min for 3 minutes to obtain a primer C component; S2.4: Before using the primer, add the primer C component to the primer B component, mix well, then add the primer B+C components to the primer A component, and finally continue to stir the mixture at a speed of 120r / min for 5h, and filter the stirred mixture with a filter cloth of 300 mesh or more to obtain the primer; The topcoat preparation method is as follows: According to the topcoat ratio of 3, nano silica sol is used as topcoat A component, formic acid and deionized water are mixed to obtain topcoat C component, polydimethylsiloxane and methyltrimethoxysilane are mixed to obtain topcoat B component, and before using the topcoat, the topcoat C component is added to the topcoat B component, and after mixing evenly, the topcoat B+C components are added to the topcoat A component, and finally the mixed liquid is put into a blender and stirred at a speed of 120r / min for 6 hours, and the stirred mixture is filtered using a filter cloth with a mesh size of 300 or more to obtain the topcoat.

[0031] The specific steps of the coating method are as follows: S1.1: The pot surface is first sandblasted with 80-mesh brown corundum at a distance of 70 mm and a blasting angle of 80°. Glass beads are then used for a second sandblasting at a distance of 50 mm and a blasting angle of 60° to form a surface with a roughness of Ra=4.0. After the second sandblasting, nitrogen is purged for 0.5 h at a nitrogen purging flow rate of 10 m / s. After purging, primer is sprayed on the pot surface at a spraying distance of 30 cm and a spraying rate of 60 mm / s. The primer is dried by laser drying at a laser power of 300 W, a temperature of 50°C, and an irradiation time of 5 min. S1.2: Etching the surface of the pot after the primer is dried to obtain a relief etched pot, and then polishing and grinding are performed. The polishing and grinding parameters are: using a grinding head composed of 2000 mesh elastic modules to grind at 0.4 MPa for 5 seconds, and then purging with nitrogen for 5 minutes. The nitrogen purge flow rate is 10 m / s. After purging, spraying the topcoat on the polished and ground pot surface. The spraying parameters of the topcoat are: spraying distance 30 cm, spraying rate 70 mm / s; S1.3: The pot after spraying the topcoat is baked and cured. The baking and curing parameters are first baked at 100°C for 7 minutes at a low temperature, and then baked at 300°C for 15 minutes to complete the coating of the ceramic coating.

[0032] Comparative Example 1 In this comparative example, only brown corundum was used for sandblasting during the coating process, and the remaining steps were consistent with those in Example 1.

[0033] Comparative Example 2 In this comparative example, only glass beads were used for sandblasting during the coating process, and the remaining steps were consistent with those in Example 1.

[0034] Comparative Example 3 In this comparative example, no polishing or grinding treatment is performed during the coating process, and the remaining steps are consistent with those of Example 1.

[0035] Comparative Example 4 In this comparative example, no drying and curing treatment is performed during the coating process, and the remaining steps are consistent with those of Example 1.

[0036] Comparative Example 5 In this comparative example, the nano-silica sol is not subjected to hydrophilic modification in the preparation of the primer, and the remaining steps are consistent with those in Example 1.

[0037]

[0038]

[0039] Experiments have shown that secondary sandblasting, polishing, grinding, and drying and curing treatments during the coating process effectively improve the performance of the ceramic coating.

[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for coating a ceramic coating for a relief etching pot, characterized in that: The ceramic coating includes a primer and a topcoat. The coating method includes the following specific steps: S1.1: The pot surface is first sandblasted with 80-mesh brown corundum at a distance of 70 mm and an angle of 80°, and then sandblasted with glass beads for a second time at a distance of 50 mm and an angle of 60° to form a surface with a roughness of Ra=3.0~4.

0. After the second sandblasting, nitrogen is purged for 0.5 h. After purging, primer is sprayed on the pot surface, and the primer is dried using a laser drying method; S1.2: etching the surface of the pot after the primer is dried to obtain a relief etching pot, polishing and grinding the pot after etching, and nitrogen purging is performed again for 5 minutes. After purging, topcoat is sprayed on the polished and ground pot surface; S1.3: The pot after spraying the topcoat is baked and cured to complete the coating of the ceramic coating.

2. A method for coating a ceramic coating for a relief etching pot according to claim 1, characterized in that: The primer formula is, by mass percentage, 20-30% hydrophilic modified nano silica sol, 5-15% inorganic pigment, 5-10% silica filler, 5-10% hollow glass microspheres, 30-40% ethyl orthosilicate, 1-5% formic acid, and 5-10% deionized water; The preparation method of hydrophilic modified nano silica sol is as follows: Aminopropyl triethoxysilane and nano-silica sol are mixed in a volume ratio of 1:10, and then 0.2wt% of 1M ammonia water is added, and the mixture is stirred at a speed of 150r / min. The temperature is raised to 40°C while stirring, and the stirring time is 2h. After the temperature is maintained at 40°C, 2wt% of polyethylene glycol 2000 is added, and the speed is increased to 200r / min. The stirring is continued for 0.5h. After the stirring is completed, the mixture is cooled to room temperature, and the mixture is first washed with ethanol and then washed with deionized water to obtain a hydrophilic modified nano-silica sol; The preparation method of the primer is as follows: S2.1: Put the inorganic pigment and silica filler into a ball mill according to proportion and grind them at 20-25°C. The speed of the ball mill is 400r / min. The grinding time is 1-2h to obtain a mixed powder. S2.2: Disperse the mixed powder and hollow glass microspheres in the hydrophilic modified nano-silica sol, and ultrasonicate for 2-3 hours to obtain the primer A component after dispersion; S2.3: Take ethyl orthosilicate as primer B component according to the proportion, put formic acid and deionized water into a mixer and stir at a speed of 200 r / min for 3 to 5 minutes to obtain primer C component; S2.4: Before using the primer, add the primer C component to the primer B component, mix well, then add the primer B+C components to the primer A component, and finally continue to stir the mixture at a speed of 120r / min for 5h, and filter the stirred mixture using a filter cloth with a mesh size of 300 or more to obtain the primer.

3. A coating method for a ceramic coating for a relief etching pot according to claim 1, characterized in that: The topcoat formula is, by mass percentage, 30-40% nano silica sol, 40-50% methyltrimethoxysilane, 1-5% formic acid, 1-5% polydimethylsiloxane, and 10-20% deionized water; The preparation method of the topcoat is as follows: According to the proportion, nano-silica sol is respectively used as the topcoat component A, formic acid and deionized water are mixed to obtain the topcoat component C, polydimethylsiloxane and methyltrimethoxysilane are mixed to obtain the topcoat component B, the topcoat component C is added to the topcoat component B before the topcoat is used, and after the topcoat B+C components are evenly mixed, the mixed liquid is finally put into a blender and stirred at a speed of 120 r / min for 4 to 6 hours, and the stirred mixture is filtered through a filter cloth with a mesh size of 300 or more to obtain the topcoat.

4. The method for coating a ceramic coating for a relief etching pot according to claim 1, characterized in that: The purge flow rate of nitrogen in S1.1 is 10 m / s.

5. The method for coating a ceramic coating for a relief etching pot according to claim 1, characterized in that: The spraying parameters of the primer in S1.1 are spraying distance 30 cm and spraying rate 60 mm / s.

6. The method for coating a ceramic coating for a relief etching pot according to claim 1, characterized in that: The parameters of the laser drying method in S1.1 are: laser power 300 W, temperature 50° C., and irradiation time 3 to 5 min.

7. A method for coating a ceramic coating for a relief etching pot according to claim 1, characterized in that: The parameters of the polishing and grinding process in S1.2 are to use a grinding head composed of 2000 mesh elastic modules and grind at 0.3-0.5 MPa for 3-5 seconds.

8. The method for coating a ceramic coating for a relief etching pot according to claim 1, characterized in that: The purge flow rate of nitrogen in S1.2 is 10 m / s.

9. The method for coating a ceramic coating for a relief etching pot according to claim 1, characterized in that: The spraying parameters of the topcoat in S1.2 are a spraying distance of 30 cm and a spraying rate of 70 mm / s.

10. The method for coating a ceramic coating for a relief etching pot according to claim 1, characterized in that: The parameters for the baking and curing in S1.3 are first baking at 100° C. for 7 minutes at a low temperature, and then baking at 300° C. for 15 minutes.

Citation Information

Patent Citations

  • Modified silicon dioxide sol, preparation method and application thereof

    CN101338082A

  • Hydrophilic modified silica sol and application thereof in preparation for hydrophilic anti-fog wear-resistant coating

    CN104725640A

  • Manufacturing method of cookware scale line and cookware

    CN108080233A

  • Method for preparing wear-resistant stain-resistant corrosion-resistant coating on surface of aluminum alloy through plasma treatment

    CN109731758A

  • Ceramic coating for etching pot as well as preparation method and application of ceramic coating

    CN117384546A

Cited By

  • A high-strength and high-toughness ceramic coating and its use method

    CN119752323A

  • High-toughness carbon steel composite board and preparation process thereof

    CN119910964A